Small RNAs: an ideal choice as sperm quality biomarkers - Mehta, Poonam; Singh, Rajender (Frontiers in Reproductive Health, 2024)
Spermatozoa were classically known as vehicles for the delivery of the paternal genome to the oocyte. However, in 1962, spermatozoa were discovered to carry significant amounts of RNA in them, which raised questions about the significance of these molecules in such a highly specialized cell. Scientific research in the last six decades has investigated the biological significance of sperm RNAs by various means. Irrespective of what sperm RNAs do, their presence in spermatozoa has attracted attention for their exploitation as biomarkers of fertility. Research in this direction started in the year 2000 and is still underway. A major hurdle in this research is the definition of the standard human sperm RNAome. Only a few normozoospermic samples have been analyzed to define the normal sperm RNAome. In this article, we provide a perspective on the suitability of sperm RNAs as biomarkers of fertility and the importance of defining the normal sperm RNAome before we can succeed in identifying RNA-based biomarkers of sperm quality and fertility. The identification of sperm RNA biomarkers of fertility can be exploited for quality screening of donor sperm samples, explain infertility in idiopathic cases, and RNA therapeutics for the treatment of male infertility.